ACSM's nutrition for exercise science - Benardot, Dan (Philadelphia : Wolters Kluwer Health, 2019)
'New from the American College of Sports Medicine! This clear and highly applied overview of exercise nutrition illustrates difficult concepts using real-world examples and case studies that allow students to put learning into practice. Well-known author Dan Benardot draws on his vast experience as an instructor, scientist, and practitioner to craft an engaging and factual resource that makes the nutrition of exercise science accessible. Written at a level appropriate for both exercise science majors and non-majors, this practical book is packed with helpful in-text learning aids and stunning visuals that bring concepts to life. As an ACSM publication, this text offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world. eBook available. Faster, smarter, and more convenient, today's eBooks can transform learning. These interactive, fully searchable tools offer24/7 access on multiple devices,the ability to highlight and share notes, and much more. Case studies with discussion questions in every chapter show real-world application of the science of nutrition. Important Factors to Consider boxes throughout chapters summarize key points. Practical advice and clear explanations in every chapter prepare students for effective practice. In-text learning aids, including Chapter Objectives, boxed Key Terms, bulleted Chapter Summaries, and multiple-choice Chapter Questions, help students master the content of the course. Practical Application Activity boxes that challenge students to get actively involved with the content include such activities as using a nutrition tracker to assess their diet for a full day and analyze their energy balance'--
'ACSM's Textbook of Sports Nutrition a textbook for exercise science students that provides a clear and practical overview of the science of nutrition as it applies'--
This book includes online access at http
Includes bibliographical references and index.
Keywords: Athletes -- Nutrition; Exercise -- Physiological aspects